EFEK METODE FABRIKASI TERHADAP SIFAT MEKANIK PADA MATERIAL KOMPOSIT SANDWICH 3C3 KARBON UD 12 K 0°/DIVINYCELL CORE - Muzayadah, Nurul Lailatul Muzayadah; Hardiyant, Indah Fitri; Nugroho, Afid Nugroho; Aritonang, Rian Suari Aritonang; Nurtiasto, Taufiq Satrio Nurtiasto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Sandwich composites are engineering materials that can be optimized and replaced with metals, mainly applied in aircraft fields because of their high strength-to-weight ratio. The quality of the composite sandwich structure depends on which fabrication method is applied. The methods used in this study are vacuum bagging, VARI, and VARI + post-curing. In vacuum bagging methods, fiber and resin are laminated manually and then covered with plastic bagging. The plastic is connected to a vacuum pump using a hose to suck the air out. Then, the VARI (Vacuum Assisted Resin Infusion) method utilizes vacuum pressure from a vacuum pump to flow resin to the laminated area of the fibers. Therefore, this study applies various methods to determine possible differences in product yields in terms of complex parts, thickness, and mechanical properties of 3C3 Carbon Sandwich Composite UD12K 0°/DVC. The results of the research concluded that the optimal method to produce high mechanical properties is obtained from the VARI method, as seen from the results of the three-point. The bending test is 26.07 MPa, better than the vacuum bagging test, which is only 17.53 MPa. The post-curing also increased mechanical properties for the flatwise test at 4082.1 MPa, 3204.2 N for the edgewise test, and 38.05 N for the three-point bending test. The VARI method is also supported by showing the surface morphology structure from the three-point. The bending flexural test shows a tight and dense structure so that the bond between the matrix and the fiber is perfectly bonded.